2019
DOI: 10.1038/s41467-019-13606-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural order as a genuine control parameter of dynamics in simple glass formers

Abstract: Glass transition is characterised by drastic dynamical slowing down upon cooling, accompanied by growing spatial heterogeneity. Its rationalisation by subtle changes in the liquid structure has been long debated but remains elusive, due to intrinsic difficulty in detecting the underlying complex structural ordering. Here we report that structural order parameter characterising local packing capability can well describe the glassy dynamics not only macroscopically but also microscopically, no matter whether it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 57 publications
(93 reference statements)
13
80
0
Order By: Relevance
“…Typically, the relaxation time τ of hard-sphere systems increases with volume fraction while approaching dense-packed states ( 7 9 , 41 ), which is experimentally observed for ϕ ≤ 0.545 (region I). This behavior can be described by a Vogel-Fulcher-Tammann (VFT) law ( 7 , 14 , 21 ) with the so-called fragility index D , a VFT volume fraction ϕ VFT , and a scaling time τ 0 . We find D = 0.35, which is in good agreement with previous studies ( 7 ), and ϕ VFT = 0.56.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the relaxation time τ of hard-sphere systems increases with volume fraction while approaching dense-packed states ( 7 9 , 41 ), which is experimentally observed for ϕ ≤ 0.545 (region I). This behavior can be described by a Vogel-Fulcher-Tammann (VFT) law ( 7 , 14 , 21 ) with the so-called fragility index D , a VFT volume fraction ϕ VFT , and a scaling time τ 0 . We find D = 0.35, which is in good agreement with previous studies ( 7 ), and ϕ VFT = 0.56.…”
Section: Resultsmentioning
confidence: 99%
“…A recent simulation study on liquids has shown a nontrivial three-dimensional (3D) structure that has been identified by higher-order correlations ( 20 ). Furthermore, orientational order, such as an interplay of crystal-like and icosahedral order, appears to play a key role in the glass transition ( 7 , 9 , 11 , 14 , 21 ). XCCA can contribute to identify orientational order via higher-order correlations ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Explicit formulation of the inference problem in terms of partial correlations, see Eq. (21), provides a method to quantify the respective contribution of geometry, local density and composition to structure. The overlap between communities inferred from Eq.…”
Section: Discussionmentioning
confidence: 99%
“…(18) and Eq. (21). As in previous work on network-theoretic community detection [37], we have used a simple local optimization algorithm to find the maxima of I(k; s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation